Risk Assessment of Buildings due to Lightning Impulses: A Case Study at College of Science and Technology - Tenzin, Namgay (Bhutan Journal of Research and Development, 2023)
Lightning Impulse protection has become important aspect of any electrical installation due to its destructive impacts. Due to changing weather patterns the intensity of lightning has been increasing over the years. The impacts due to lightning impulses usually in domestic installations are destructive and often the electrical supply lines are damaged with service interruptions. College of Science and Technology (CST), is located at foothills of the Himalayas with sub-tropical climate and it experiences minimum of 12-16 lightning events per square kilometers per year. Therefore, the region experiences severe lightning events especially in the late spring, summer and early autumn seasons. In this research a risk assessment of building electrical installations is being analyzed to manage and mitigate the impacts due to lightning impulses by using IEEE 62305 standard to evaluate the risks. The risk assessment for case study location at College of Science and Technology, shows that the earth resistance is beyond the permissible limit as per national and international standards and lightning protection systems are being proposed at various locations in the campus. The current study does not include all the buildings of the CST campus but only selected buildings are assessed for impacts due to lightning impulses.